The Effect of Fatigue on Lower Extremity Joint Kinematics and Performance - Shelley Payne; Sarah Alloto; Joe Wilkins; Ashley Simons (Bowling Green State University, 2023)
ACL injuries are multifactorial in nature meaning they can be the result of faulty biomechanics, individual genetic predisposition, or environmental factors (Alentorn- Geli et al., 2009). A focus of most healthcare professionals including physical therapists and athletic trainers includes the screening for preventable risk factors for non- contact ACL injuries. Preventable risk factors include asymmetry between a person's limbs, decreased hamstring strength, increased muscle fatigue, decreased landing angle of hip and knee Tlexion, increased valgus landing, and lack of Tlexibility in the hip internal rotators (Brophy, 2021). Given the short and long-term negative consequences of an ACL injury, it is important for healthcare providers to explore screening and prevention techniques to employ with at-risk athletic populations.